Hak asasi manusia di era digital: Tantangan privasi dan kebebasan berpendapat - syahid, muchammad iqbalgntg (Maliki Interdisciplinary Journal, 2026)
This study examines the role of Pancasila as state morality in protecting human rights in Indonesia amid the digital era and globalization. Using a normative juridical approach and qualitative analysis, this research analyzes the relevance of Pancasila values—particularly the second principle of "Just and Civilized Humanity"—as philosophical and normative foundations for human rights protection. The aspects examined include personal data protection under Law No. 27 of 2022, freedom of expression on social media, and the impact of information technology on human rights practices. The results indicate that Pancasila has potential as a holistic framework, but its implementation is hindered by low digital literacy, weak oversight capacity, and the incomplete internalization of Pancasila values in society. The study recommends consistent law enforcement, digital literacy education, and harmonization of Pancasila values with international human rights norms.